Ethics in The Teaching Profession: A Virtue Ethics Approach to Teaching Ethics - OKPO, Odumayak (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2022)
This paper examines the application of the normative ethical theory of virtue ethics to some ethical issues and dilemmas in the teaching profession in Nigeria. The paper is concerned with teaching as a profession, that is, professional ethics—teaching ethics. It argues that many unethical behaviours in the teaching profession, such as aiding and abetting examination malpractice by the students, exploitation of students, teacher absenteeism, and corrupt practise (such as having canal knowledge of a learner, bribery, and an indecent relationship with a learner, just to mention a few), among others, constitute ethical issues in the teaching profession. And these unethical behaviours have many negative implications and consequences for teachers, students, the teaching profession, the education system, and society as a whole. It concludes that ethics is a crucial element in the teaching profession and is essential to a teacher’s professional life. Vicious acts and unethical misconduct by teachers are harmful to the teaching profession, student education, and the nation’s educational system, but virtuous acts such as honesty, integrity, fairness, trustworthiness, practical wisdom, and empathy, among others.